Sensors: Nanoparticle‐Structured Highly Sensitive and Anisotropic Gauge Sensors (Small 35/2015). Issue 35 (10th September 2015) - Zhao, Wei; Luo, Jin; Shan, Shiyao; Lombardi, Jack P.; Xu, Yvonne; Cartwright, Kelly; Lu, Susan; Poliks, Mark; Zhong, Chuan‐Jian
<x xml:space="preserve">Abstract</x> A gold nanoparticle structured thin‐film sensor with unusually high and anisotropic gauge factors is demonstrated by C. J. Zhong and co‐workers on page 4509. This sensing characteristic is tunable by the nanostructural parameters and the self‐assembling or printing method, and has important implications for the design of gauge sensors for the highly sensitive detection of deformations in complex sensing environments such as wearable electronics and skin sensors.